Pemberdayaan ekonomi masyarakat desa kayulaut melalui UMKM komunitas kue khas Bika bakar kayulaut dengan strategi culinary fashion - Jureid; Syarifah Nasution, Dina; Siregar, Nurintan (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
This Community Service is carried out by Lecturer of English Tadris Study Program STAIN Madina and Sharia Economics Lecturer Stain Madina with the method of Asset Based Community Development (ABCD). The implementation of Community Service is supported by various parties, in this case the Head of Kayulaut Village and Naposo Nauli Bulung of Kayulaut Village. And the Kayulaut Bika Bakar Cake MSME Community One of the reasons for choosing this village is because Kayulaut Village has the potential for a prosperous life through traditional bika bakar cake cooking skills by its residents, but it is known that in recent years the sales turnover of Bika Bakar Cake producers has decreased drastically due to several things, including packaging that still uses plastic bags and limited marketing access. Partner products cannot compete with modern pastry products made by already large businesses because there is not enough promotion. Partners still use simple tools – causing fatigue because they are continuously around the fire stove, so that the production of bika bakar produced is not optimal in quantity or quality.so that Kue Bika Bakar Kayulaut no longer meets trade turnover like a few years ago. The stages of Community Service carried out are divided into three stages, namely; Socialization of Program Activities, Implementation and Evaluation. Community Service Lasted from 08.00 WIB until it was completed for three days starting from the preparation of the activity, attended by 70 participants. The subject matter conveyed Through this activity; Logo / branding, packaging, and e-commerce. With the Community Service activities, the economic empowerment of the Kayulaut village community through MSMEs of the typical Bika bakar kayulaut cake community with a culinary fashion strategy is expected to increase the production turnover of Kayulaut Bika Bakar Cake so that the people of Kayulaut Village are more prosperous as MSME actors of Kayulaut Cake.